3D Instantaneous Reconstruction of Turbulent Industrial Flames Using Computed Tomography of Chemiluminescence (CTC). (29th October 2018) - Unterberger, A.; Röder, M.; Giese, A.; Al-Halbouni, A.; Kempf, A.; Mohri, K.
Abstract : Computed Tomography of Chemiluminescence (CTC) was used to reconstruct the instantaneous three-dimensional (3D) chemiluminescence field of a high-power industrial flame, which was made optically accessible, for the first time. The reconstruction used 24 projections that were measured simultaneously, in one plane and equiangularly spaced within a total fan angle of 172.5°. The 3D results were examined by plotting both vertical and horizontal slices, revealing highly wrinkled structures with good clarity. The results presented are one of a series of experimental demonstrations of CTC applications to turbulent gaseous flames. The work reveals the potential to use any kind of luminescence measurement, such as emission from heated particles in coal-fired flames, for analysis of the flame shape directly in 3D.